Inhibition test of noni fruit extract (Morinda citrifolia L.) against Candida albicans growth: Uji daya hambat ekstrak buah mengkudu (Morinda citrifolia L.) terhadap pertumbuhan Candida albicans - Munov, Aqilla Patricia; Mailiza, Fitria; Kornialia (Makassar Dental Journal PDGI Makassar, 2025)
Candidiasis is a fungal infection caused by overgrowth of Candida albicans species. Noni fruit (Morinda citrifolia L.) is one of the plants that has antifungal activity through the content of compounds such as flavonoids, saponins, alkaloids, terpenoids, pheno-lics, and tannins. This study discusses the inhibition of noni fruit extract (NFE) at concentrations of 10%, 15%, and 20% against the growth of C.albicans using laboratory experimental methods with a descriptive approach and using a one shot case study de-sign. Noni fruit was extracted using maceration method with 96% methanol solvent. A total of 18 samples of C.albicans were divi-ded into 3 treatments, namely 10%, 15% and 20% concentrations. The inhibition test was carried out using the pitting diffusion me-thod, while the measurement of the inhibition zone using a caliper showed that 10% NFE had an inhibition that was categorised as moderate, 15% was categorised as strong, and 20% was also categorised as strong. It was concluded that noni fruit extract has inhibitory power against the growth of C.albicans, with the best effectiveness at a concentration of 20% which showed a strong inhibition category.